NURSING CONTRIBUTIONS TO THE SELF-CARE OF PATIENTS WITH CHRONIC KIDNEY DISEASE: : A REFLECTIVE STUDY FROM THE VIEWPOINT OF CARE - de Castro , Kemely; Christiny, Larissa; Alves Ribeiro, Wanderson; do Carmo Neves, Keila; de Paula, Enimar; Silva Lima, Daiana; John Mota de Oliveira , Elton; Nascimento Barcellos, Laila; Laine da Conceição Dias, Lilian; Motta Moreira de Souza, Erica; Kelly Souza Motta Alcoforado, Greyce (Health and Society, 2022)
Chronic kidney disease (CKD), evidenced by the gradual loss of kidney function in an insidious and asymptomatic way, appears in this scenario as a relevant global public health problem, due to the expressive growth of its prevalence, impacts of its chronic complications and high cost. social and economic. The study aims to reflect on the contributions of nursing in the self-care of patients with Chronic Kidney Disease. This is a descriptive, qualitative study of the reflective analysis type. Through this research, it was possible to observe the importance of care-educational actions of nurses during the diagnosis and treatment of patients with CKD. These actions are intended to boost the process of adaptation to their new treatment routine, these results are achieved through comprehensive care for the patient in rehabilitation, constituting a link between the professional nurse and the patient in the rehabilitation process.